Perancangan dan Implementasi Aplikasi Mobile Buku Kas Menggunakan Metode User-Centered Design untuk Mendukung Pengelolaan Keuangan Para Pelaku UMKM - Suliwa Yudha Adinata; Lely Panca Andriyanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The rapid development of information technology has provided convenience in various aspects of life, including financial management. Proper financial management is one of the determining factors for business sustainability and growth, particularly for Micro, Small, and Medium Enterprises (MSMEs), which serve as one of the main pillars of the national economy. However, many MSME owners still do not have the habit of recording daily transactions regularly due to limited time and the lack of simple recording tools. This problem affects the ability of MSME owners to accurately monitor cash flow, distinguish personal and business finances, and make business decisions based on valid data. Manual recording using physical cash books is also considered inefficient, prone to human error, easily lost or damaged, and difficult to recapitulate or analyze quickly when needed. This condition is further exacerbated by the low level of digital literacy among some MSME owners and the limited availability of financial recording applications that are truly suitable for the characteristics of micro-enterprises, namely simple, lightweight, easy to learn, and accessible anytime through mobile devices without requiring special training. This study aims to design and develop a mobile cash book application to assist MSME owners in recording daily income and expenses efficiently. The method used is User-Centered Design (UCD), which places user needs as the main focus throughout the process, including requirements identification, interface design, prototyping, and user evaluation. The application was developed using Kotlin in Android Studio with local data storage using SQLite synchronized with a MySQL database on the server side. Functional testing was conducted using the Black Box Testing method, while user acceptance evaluation was performed through a Likert-scale questionnaire involving 35 respondents based on three aspects: Usability, UI/UX, and Efficiency. The results showed that the application functioned properly and received very positive responses from users across all evaluation aspects, demonstrating that the implementation of UCD can improve user satisfaction in independently managing finances through mobile devices. This research contributes to the development of an Android-based mobile cash book application that provides features for recording income and expenses, transaction category management, financial report visualization, PDF report export, and transaction recording reminders. Furthermore, the implementation of synchronization mechanisms between SQLite and MySQL enables transaction recording even when an internet connection is unavailable, with data updates performed when the connection becomes available again.